(untitled) (Proceedings OPTIMAL, 2025)
Background: Pain remains one of the most prevalent and debilitating symptoms experienced by individuals with cancer, adversely affecting their quality of life, treatment adherence, and psychosocial well-being. In Indonesia and other low-resource settings, cancer pain management continues to face systemic challenges, including limited access to palliative care, inadequate opioid availability, low health and digital literacy, and regulatory constraints. With the growing integration of digital technology in healthcare, electronic health (e-Health) interventions such as mobile applications, telemedicine, and mHealth platforms have emerged as promising strategies. This study aims to systematically map the types of e-Health interventions applied in cancer pain management, examine their effectiveness, and identify implementation barriers and opportunities, particularly in developing country contexts. Method: This study used a scoping review approach following the PRISMA-ScR guideline and PCC framework (Population: cancer patients; Concept: e-Health interventions; Context: pain management). Literature was searched in four databases (PubMed, Scopus, ScienceDirect, Google Scholar) for studies published between 2016 and 2024. Ten studies met the inclusion criteria and were analyzed. Results: Identified e-Health interventions included mobile applications, telemedicine, CBT-based tools, telerehabilitation, and integrated digital ecosystems. Most interventions were effective in reducing pain intensity, enhancing self-management, improving adherence, and providing psychosocial support. Interactive features such as chat functions and video-based coping strategies were especially impactful. Conclusion: e-Health presents a promising solution for cancer pain management by supporting both physical and psychosocial aspects of care. With proper adaptation and integration, these interventions can strengthen oncology services and patient outcomes in low-resource environments.